Resistance evolution to basil essential oil: how selection pressure shapes tolerance and fitness costs in Aphis craccivora - Prangthip Parichanon; Linda Abenaim; Roberta Ascrizzi; Guido Flamini; Maria Cristina Echeverría; Sania Ortega-Andrade; Barbara Conti (Environmental Science and Pollution Research, 2026)

Chestnut tannin induces gut degeneration in Aedes albopictus mosquito larvae - Linda Abenaim; Priscilla Farina; Angela Rosa Cuzzola; Loretta Guidi; Romano Dallai; David Mercati; Erika Carla Pierattini; Barbara Conti; Alessandro Mandoli (Environmental Science and Pollution Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The mite, the bug, and the nematode: Assessing the efficacy of three biological control agents against Echinothrips americanus (Thysanoptera: Thripidae) - Fabio Marino; Linda Abenaim; Giuseppe Conte; Daniele Marraccini; Priscilla Farina; Barbara Conti (Crop Protection, 2026)

Transcript-protein discrepancy of glutamatergic receptor subunits in human iPSC-derived neurons: Implications for neurotoxicity testing - Melania Maria Serafini; Miriam Midali; Giacomo Grumelli; Alessandro Cutarelli; Marina Marinovich; Luciano Conti; Barbara Viviani (Toxicology Letters, 2026)

Antifungal activity and sensory analyses of chitosan aromatized with essential oils for the protection of fresh oranges and apples - Mario Riolo; Federico La Spada; Priscilla Farina; Soumia El Boumlasy; Roberta Ascrizzi; Francesca Venturi; Isabella Taglieri; Nunzio Tuccitto; Antonella Pane; Samuel Álvarez-García; Barbara Conti; Gianfranco Romanazzi; et al. (Postharvest Biology and Technology, 2026)

Calliphora vomitoria: both the beauty and the beast - Priscilla Farina; Barbara Conti; Angelo Canale; Andrea Lucchi; Stefano Vanin; Giovanni Benelli (Journal of Pest Science, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Insect-based biopolymers from Orthoptera: An emerging resource for sustainable and active food packaging - Oscar Zannou; Barbara Conti; Linda Abenaim; João K. Lopes; Paula Barciela; Custódio L. Roriz; Miguel A. Prieto; Sandrina A. Heleno; Marcio Carocho; Gulden Goksen (Trends in Food Science & Technology, 2026)

Mandarin essential oil-flavoured bio-based active packaging for quality preservation and fungal control in fresh produce - Prangthip Parichanon; Marco Santin; Marwa Khemakhem; Thierry Falher; Arianna Petrucci; Diego Mencarini; Sabrina Sarrocco; Barbara Conti; Antonella Castagna (Postharvest Biology and Technology, 2026)

Embryotoxicity of polystyrene microplastics, alone and conjugated with bisphenol A, in the black sea urchin Arbacia lixula: A multi-biomarker approach - Maria Concetta Eliso; Barbara Billè; Giuseppe De Marco; Eloise Pulvirenti; Federica Dal Bello; Paola Rapisarda; Patrícia Pereira; Mariachiara Galati; Gea Oliveri Conti; Margherita Ferrante; Patrizia Bovolin; Maria Maisano; et al. (Journal of Hazardous Materials, 2025)

Exploring the plastivorous activity of Hermetia illucens (Diptera Stratiomyidae) larvae - Linda Abenaim; David Mercati; Alessandro Mandoli; Joachim Carpentier; Grégoire Noël; Barbara Conti; Rudy Caparros Megido; Romano Dallai (Environmental Science and Pollution Research, 2025)

The aromatic plant essential oils and their hormetic effect on Rhyzopertha dominica (Coleoptera: Bostrichidae) - Prangthip Parichanon; Roberta Ascrizzi; Maria Cristina Echeverría; Priscilla Farina; Ylenia Pieracci; Guido Flamini; Federica Semprucci; Loretta Guidi; Eleonora Grassi; Theodora Isavella Gogou; Sania Ortega-Andrade; Barbara Conti (Crop Protection, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Ecotoxicological assessment of basil essential oil on soil nematode communities - Catani Linda; Grassi Eleonora; Guidi Loretta; Farina Priscilla; Tani Camilla; Conti Barbara; Annibaldi Anna; Girolametti Federico; Ascrizzi Roberta; Flamini Guido; Da Costa Monteiro Luana; Semprucci Federica (Environmental Pollution, 2025)

Soft soap and linalool as potential management tools for Philaenus spumarius (Hemiptera: Aphrophoridae), vector of Xylella fastidiosa - Linda Abenaim; Priscilla Farina; Alessandro Mandoli; Giuseppe Conte; Barbara Conti (Crop Protection, 2025)

Cellular pathway disturbances elicited by realistic dexamethasone concentrations in gills of mussel Mytilus galloprovincialis as assessed by a multi-biomarker approach - Giuseppe De Marco; Antonio Cristaldi; Maria Concetta Eliso; Gea Oliveri Conti; Mariachiara Galati; Barbara Billè; Mery Terranova; Vincenzo Parrino; Tiziana Cappello; Margherita Ferrante; Maria Maisano (Environmental Toxicology and Pharmacology, 2025)

Chitosan/mandarin essential oil-based films on citrus fruits for the control of the medfly attack and to prevent the occurrence of grey and blue mould in post-harvest - Prangthip Parichanon; Priscilla Farina; Isabel Vicente; Marco Cesarini; Eliverta Hotaj; Sabrina Sarrocco; Elisa Pellegrini; Barbara Conti (Journal of Stored Products Research, 2024)

Liabilities of essential oils as insect repellents - Priscilla Farina; Barbara Conti (Current Opinion in Environmental Science & Health, 2024)

Performance of Hermetia illucens (Diptera: Stratiomyidae) larvae reared on organic waste diets and pupal chitin and chitosan yield - Christina Adamaki-Sotiraki; Linda Abenaim; Alessia Mannucci; Christos I. Rumbos; Stefano Bedini; Antonella Castagna; Giuseppe Conte; Monica Tognocchi; Victor Dolianitis; Christos G. Athanassiou; Barbara Conti (Environmental Science and Pollution Research, 2024)

Physicochemical and repellent properties of chitosan films loaded with essential oils for producing an active packaging effective against the food pest Sitophilus oryzae - Tasnim Djebbi; Roberta Ascrizzi; Stefano Bedini; Priscilla Farina; Chiara Sanmartin; Jouda Mediouni Ben Jemâa; Maria Francesca Bozzini; Guido Flamini; Barbara Conti (Journal of Stored Products Research, 2024)

The protective combined effect of chitosan and essential oil coatings on cheese and cured meat against the oviposition of Piophila casei - Prangthip Parichanon; Roberta Ascrizzi; Camilla Tani; Chiara Sanmartin; Isabella Taglieri; Monica Macaluso; Guido Flamini; Ylenia Pieracci; Francesca Venturi; Barbara Conti (Food Bioscience, 2023)

Short-term exposure to polystyrene microplastics hampers the cellular function of gills in the Mediterranean mussel Mytilus galloprovincialis - Giuseppe De Marco; Maria Concetta Eliso; Gea Oliveri Conti; Mariachiara Galati; Barbara Billè; Maria Maisano; Margherita Ferrante; Tiziana Cappello (Aquatic Toxicology, 2023)

Single and combined effects of caffeine and salicylic acid on mussel Mytilus galloprovincialis: Changes at histomorphological, molecular and biochemical levels - Sabrine Afsa; Giuseppe De Marco; Antonio Cristaldi; Alessia Giannetto; Mariachiara Galati; Barbara Billè; Gea Oliveri Conti; Hedi ben Mansour; Margherita Ferrante; Tiziana Cappello (Environmental Toxicology and Pharmacology, 2023)

Different molecular changes underlie the same phenotypic transition: Origins and consequences of independent shifts to homostyly within species - Emiliano Mora‐Carrera; Rebecca L. Stubbs; Barbara Keller; Étienne Léveillé‐Bourret; Jurriaan M. de Vos; Peter Szövényi; Elena Conti (Molecular Ecology, 2023)
The repeated transition from outcrossing to selfing is a key topic in evolutionary biology. However, the molecular basis of such shifts has been rarely examined due to lack of knowledge of the genes controlling these transitions. A classic example of mating system transition is the repeated shift from heterostyly to homostyly. Occurring in 28 angiosperm families, heterostyly is characterized by the reciprocal position of male and female sexual organs in two (or three) distinct, usually self‐incompatible floral morphs. Conversely, homostyly is characterized by a single, self‐compatible floral morph with reduced separation of male and female organs, facilitating selfing. Here, we investigate the origins of homostyly in Primula vulgaris and its microevolutionary consequences by integrating surveys of the frequency of homostyles in natural populations, DNA sequence analyses of the gene controlling the position of female sexual organs ( CYPᵀ ), and microsatellite genotyping of both progeny arrays and natural populations characterized by varying frequencies of homostyles. As expected, we found that homostyles displace short‐styled individuals, but long‐style morphs are maintained at low frequencies within populations. We also demonstrated that homostyles repeatedly evolved from short‐styled individuals in association with different types of loss‐of‐function mutations in CYPᵀ . Additionally, homostyly triggers a shift to selfing, promoting increased inbreeding within and genetic differentiation among populations. Our results elucidate the causes and consequences of repeated transitions to homostyly within species, and the putative mechanisms precluding its fixation in P. vulgaris . This study represents a benchmark for future analyses of losses of heterostyly in other angiosperms.

First application of an Integrated Biological Response index to assess the ecotoxicological status of honeybees from rural and urban areas - Ilaria Caliani; Tommaso Campani; Barbara Conti; Francesca Cosci; Stefano Bedini; Antonella D’Agostino; Laura Giovanetti; Agata Di Noi; Silvia Casini (Environmental Science and Pollution Research, 2021)
Understanding the effects of environmental contaminants on honeybees is essential to minimize their impacts on these important pollinating insects. The aim of this study was to assess the ecotoxicological status of honeybees in environments undergoing different anthropic pressure: a wood (reference site), an orchard, an agricultural area, and an urban site, using a multi-biomarker approach. To synthetically represent the ecotoxicological status of the honeybees, the responses of the single biomarkers were integrated by the Integrated Biological Response (IBRv2) index. Overall, the strongest alteration of the ecotoxicological status (IBRv2 = 7.52) was detected in the bees from the orchard due to the alteration of metabolic and genotoxicity biomarkers indicating the presence of pesticides, metals, and lipophilic compounds. Honeybees from the cultivated area (IBRv2 = 7.18) revealed an alteration especially in neurotoxicity, metabolic, and genotoxicity biomarkers probably related to the presence of pesticides, especially fungicides. Finally, in the urban area (IBRv2 = 6.60), the biomarker results (GST, lysozyme, and hemocytes) indicated immunosuppression in the honeybees and the effects of the presence of lipophilic compounds and metals in the environment.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Surviving in isolation: genetic variation, bottlenecks and reproductive strategies in the Canarian endemic Limonium macrophyllum (Plumbaginaceae) - Ares Jiménez; Barbara Weigelt; Arnoldo Santos-Guerra; Juli Caujapé-Castells; José María Fernández-Palacios; Elena Conti (Genetica, 2017)

Biosynthesis, mosquitocidal and antibacterial properties of Toddalia asiatica-synthesized silver nanoparticles: do they impact predation of guppy Poecilia reticulata against the filariasis mosquito Culex quinquefasciatus? - Kadarkarai Murugan; Joseph Selvaraj Eugine Venus; Chellasamy Panneerselvam; Stefano Bedini; Barbara Conti; Marcello Nicoletti; Santosh Kumar Sarkar; Jiang-Shiou Hwang; Jayapal Subramaniam; Pari Madhiyazhagan; Palanisamy Mahesh Kumar; Devakumar Dinesh; et al. (Environmental Science and Pollution Research, 2015)

Stability Evaluation of Ivermectin-Loaded Biodegradable Microspheres - Rossella Dorati; Ida Genta; Barbara Colzani; Tiziana Modena; Giovanna Bruni; Giuseppe Tripodo; Bice Conti (AAPS PharmSciTech, 2015)

Not just for beer: evaluation of spent hops (Humulus lupulus L.) as a source of eco-friendly repellents for insect pests of stored foods - Stefano Bedini; Guido Flamini; Jessica Girardi; Francesca Cosci; Barbara Conti (Journal of Pest Science, 2015)

Low genetic diversity and high levels of inbreeding in the Sinai primrose (Primula boveana), a species on the brink of extinction - Ares Jiménez; Hassan Mansour; Barbara Keller; Elena Conti (Plant Systematics and Evolution, 2014)

Ingestion toxicity of three Lamiaceae essential oils incorporated in protein baits against the olive fruit fly, Bactrocera oleae (Rossi) (Diptera Tephritidae) - Angelo Canale; Giovanni Benelli; Barbara Conti; Gabriele Lenzi; Guido Flamini; Alessandra Francini; Pier Luigi Cioni (Natural Product Research, 2013)

Volatile chemical composition and bioactivity of six essential oils against the stored food insect Sitophilus zeamais Motsch. (Coleoptera Dryophthoridae) - Alessandra Bertoli; Barbara Conti; Valerio Mazzoni; Laura Meini; Luisa Pistelli (Natural Product Research, 2011)

Hyptis suaveolens and Hyptis spicigera (Lamiaceae) essential oils: qualitative analysis, contact toxicity and repellent activity against Sitophilus granarius (L.) (Coleoptera: Dryophthoridae) - Barbara Conti; Angelo Canale; Pier Luigi Cioni; Guido Flamini; Alessandro Rifici (Journal of Pest Science, 2011)

Communally breeding Bechstein's bats have a stable social system that is independent from the postglacial history and location of the populations - GERALD KERTH; BOYAN PETROV; ANDREJ CONTI; DANIJELA ANASTASOV; MANFRED WEISHAAR; SUREN GAZARYAN; JULIE JAQUIÉRY; BARBARA KÖNIG; NICOLAS PERRIN; NADIA BRUYNDONCKX (Molecular Ecology, 2008)
Investigating macro‐geographical genetic structures of animal populations is crucial to reconstruct population histories and to identify significant units for conservation. This approach may also provide information about the intraspecific flexibility of social systems. We investigated the history and current structure of a large number of populations in the communally breeding Bechstein's bat ( Myotis bechsteinii ). Our aim was to understand which factors shape the species’ social system over a large ecological and geographical range. Using sequence data from one coding and one noncoding mitochondrial DNA region, we identified the Balkan Peninsula as the main and probably only glacial refugium of the species in Europe. Sequence data also suggest the presence of a cryptic taxon in the Caucasus and Anatolia. In a second step, we used seven autosomal and two mitochondrial microsatellite loci to compare population structures inside and outside of the Balkan glacial refugium. Central European and Balkan populations both were more strongly differentiated for mitochondrial DNA than for nuclear DNA, had higher genetic diversities and lower levels of relatedness at swarming (mating) sites than in maternity (breeding) colonies, and showed more differentiation between colonies than between swarming sites. All these suggest that populations are shaped by strong female philopatry, male dispersal, and outbreeding throughout their European range. We conclude that Bechstein's bats have a stable social system that is independent from the postglacial history and location of the populations. Our findings have implications for the understanding of the benefits of sociality in female Bechstein's bats and for the conservation of this endangered species.

Oral anti-inflammatory activity of cannabidiol, a non-psychoactive constituent of cannabis, in acute carrageenan-induced inflammation in the rat paw - Barbara Costa; Mariapia Colleoni; Silvia Conti; Daniela Parolaro; Chiara Franke; Anna Elisa Trovato; Gabriella Giagnoni (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)